An investigation of 5th grade Turkish students' performance in number sense on the topic of decimal numbers - GÜLBAĞCI DEDE, HANDE; ŞENGÜL, SARE (ELSEVIER SCIENCE BV, 2012)
The purpose of this research is to investigate the number sense of 5th grade Turkish students on the topic of decimal numbers. The research participants are composed of 121 5th grade students from two different elementary schools.. All of the students have already completed the 5th grade mathematics curriculum. The data of the research was collected by number sense test about decimal numbers (NSTDN). It contained 16 questions and four components of number sense. The results of this quantitatively analysed research have shown that the 5th grade students' number sense on decimal numbers is low. There was no significant difference in number sense between the genders. These findings are consistent with the previous researches. (C) 2012 Published by Elsevier Ltd. Selection and/or peer review under responsibility of Prof. Dr. Huseyin Uzunboylu
Keywords: number sense; decimal numbers; Turkey